Cinema of Discovery: Julien Duvivier in the 1920s - Coppola, Antonio; Dalpane, Marco; Lovsky, Fay; Thibaudeau, Gabriel (Flicker Alley, 2021)
One of the most prolific and technically proficient filmmakers in cinema history, Julien Duvivier, was idolized by the likes of directors Jean Renoir, Ingmar Bergman, and Orson Welles. Duvivier's expressive use of the camera was primarily created under the influence of poetic realist style - in fact he did much to establish the technical and aesthetic standards of French poetic realism, which won him international acclaim. For a time, he was among cinema's most celebrated directors, receiving nominations and top prizes at notable international film competitions, including the Berlin International Film Festival, the Venice Film Festival, the National Board of Review, and New York Film Critics Circle Awards. Assembled in this Blu-ray disc collection are nine of Julien Duvivier's deeply moving and imaginative early feature films from the late 1920s that showcase his innovative and prominent contribution to film history. [www.flickeralley.com]
Keywords: Blu-Ray-Disc